Analisis Prakiraan Beban Listrik Rumah Tangga dengan Menggunakan Metode Regresi - Marwan, Marwan (Politeknik Negeri Ujung Pandang, 2019)
The purpose of this research is to analyse the number of consumers and electricity load of residential house in South Makassar region for 2019. To achieved this goal, a simple linear regression method for calculating the number of consumers and multiple linear regression methods to calculate the electrical load. To analyse this study, electricity data was taken from Electricity State Company (called PLN) since 2015 to 2016. Based on the results illustrated that the number of consumers and electricity load at the end of December 2019 were 752865 and 155187128 kWh, respectively.